Fit & well : core concepts and labs in physical fitness and wellness - Fahey, Thomas D. (Thomas Davin), 1947-; Insel, Paul M.; Roth, Walton T. (New York : McGraw-Hill Higher Education, 2009)
Fit and Well offers an outstanding text and teaching package designed to help students incorporate fitness and wellness into their daily lives. It provides accurate, up-to-date coverage of the five components of health-related fitness, along with coverage of nutrition. It also gives students the practical tools they need to take charge of their wellness-related behaviors and adopt a healthier lifestyle. Chapters 1-8 of the full version of Fit and Well (15 chapters) are included in the brief edition
Includes bibliographical references and index.
College students
Keywords: Physical fitness; Health